Pengaruh Kombinasi Slow Deep Breathing, Dzikir, dan Aromaterapi Lavender terhadap Tekanan Darah pada Lansia Hipertensi di Padukuhan Kalipakis - Arif, Nadya Maulida; Noviani, Wulan (Sci-tech Journal, 2026)
Hypertension poses a significant threat for heart-related issues in older adults. Managing this condition without medication through methods like relaxation techniques, spiritual practices, and the use of essential oils is crucial. This research aimed to explore the impact of a combination of the slow deep breathing exercise (4-7-8 method), the recitation of “Astaghfirullah,” and lavender essential oil treatment on blood pressure levels. The case study focused on two senior women, Mrs. P (60 years old) and Mrs. S (61 years old), residing in Padukuhan Kalipakis. The treatment was administered daily for a duration of 15 to 30 minutes over a span of three days. Findings indicated a notable reduction in blood pressure. In the case of Mrs. P, her blood pressure dropped from 168/93 mmHg to 138/85 mmHg, while Mrs. S experienced a decrease from 141/79 mmHg to 110/66 mmHg. The combination of physiological, psychological, and spiritual elements through this integrated approach proves to be effective in lowering blood pressure among elderly individuals and may serve as an additional nursing strategy.